Long-term reserve expansion of power systems with high wind power penetration using universal generating function methods - Ding, Yi (2011)
In a power system with high wind power penetration, reliability-based reserve expansion is a major problem of system planning and operation due to the uncertainty and fast fluctuation of wind speeds. This paper studied the impact of high wind power penetration on the system reserve and reliability from long-term planning point of view utilizing universal generating function (UGF) methods. The reliability models of wind farms and conventional generators are represented as the corresponding UGFs, and the special operators for these UGFs are defined to evaluate the customer and the system reliabilities. The effect of transmission network on customer reliabilities is also considered in the system UGF. The power output models of wind turbine generators in a wind farm considering wind speed correlation and un-correlation are developed, respectively. A reliability-based reserve expansion method is proposed to determine the conventional reserve required for power systems with high wind power penetration. The IEEE-RTS has been modified to illustrate the applications of the proposed method.